An Analysis on The Principles of Arabic Textbooks for Madrasah Aliyah in Indonesia: Based on The Ministry of Education and Rusydi Ahmad Thu’aimah - Asbarin, Asbarin; Machmudah, Umi; Amalia, Nabila Nailil; Taufik, Moch (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2022)
The purpose of this study is to describe the contents of the tenth-grade Arabic textbook by Hasan Saefullah based on the 2008 Ministry of National Education standards and Ahmad Thu'aimah. The research method used is a literature study using qualitative method with descriptive content analysis techniques. The results of this study indicate that this book generally has complied with the principles of compiling the 2008 Ministry of National Education standard teaching materials. It is aligned with the principles of consistency, relevancy, and adequacy, which have been contained in competency standards and basic competencies in learning objectives. However, on the gradation principle, there is a discrepancy in the material contained in the teaching material preparation, such as the receptive and expressive language mastery section. The author places the mastery of reading skills after listening skills and grammatical mastery before speaking skills. It violates the order of language learning in general because the sequence of language learning starts from maharah istima', then maharah kalam, maharah qiroah, and finally maharah kitaba. Meanwhile, Thu'aimah standards, which includes the principles of validity, meaningfulness, and feasibility, have also been applied in the preparation of this textbook. The researchers expect that the authors of Arabic teaching materials pay more attention to several international and national standardization principles in writing Arabic teaching materials.